PERANAN KEARIFAN LOKAL DALAM PENDIDIKAN KARAKTER - Ulfah Fajarini (Sosio-Didaktika: Social Science Education Journal, 2014)
This article aims to examine on a wealth of local wisdom in Indonesia that plays a role in shaping the character education. Local wisdom will only be lasting if local knowledge implemented in concrete everyday life so that they can respond and answer the current times have changed. Local wisdom should also be implemented in state policy, for example by applying economic policy based on mutual cooperation and kinship as one manifestation of our local wisdom. To achieve that, state ideology (Pancasila) should be implemented in a variety of state policy. Thus, local knowledge will effectively function as a weapon-not just heritage-that equip people to respond and answer the current era. Preserving various elements of local wisdom, traditions and local institutions, including the norms and customs that are beneficial, can function effectively in character education, while doing study and enrichment with new wisdoms.